PENELEH, A SECOND LIFE TO AN OLD DUTCH CEMETERY - Hans Versnel (Journal of Architecture&ENVIRONMENT, 2012)
To a certain extent there is a second life to the former Dutch cemetery Peneleh inthe centre of the city of Surabaya, Indonesia. The present days obsolete conditioncan be revitalised through the needed expansion of the pasar; a recreational area to the residents of the densely populated surrounding kampung; a reuse of the former caretaker house at the entrance, which is now a Puskesmas, community health centre, and part of the graveyard can revive as monumental location to show the history.These strong points to revitalise the area are effective through a close connection with residents, planners and authorities, which can be put in aparticipatory process. Dead or alive, potentially the Peneleh area is worth to beredeveloped into an attractive residential part of Surabaya. A heritage worth to visit by domestic and foreign visitors.